2017
DOI: 10.1016/j.ajog.2017.05.046
|View full text |Cite
|
Sign up to set email alerts
|

Successful maintenance of key physiological parameters in preterm lambs treated with ex vivo uterine environment therapy for a period of 1 week

Abstract: Five preterm lambs were maintained in a physiologically stable condition for 1 week with significant growth and without clinically significant bacteremia or systemic inflammation. Although substantial further refinement is required, a life support platform based around ex vivo uterine environment therapy may provide an avenue to improve outcomes for extremely preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(68 citation statements)
references
References 53 publications
1
60
0
Order By: Relevance
“…In previous reports based on our EVE system we demonstrated healthy fetal survival for a period of hours (h), and further extended that to 336 h in a subsequent set of unpublished experiments. [7][8][9][10] Other investigators have reported the successful application of artificial-placenta based therapies for up to h with similar concepts and extracorporeal gas exchange systems. [11][12][13][14] Accordingly, the feasibility of long survival with a pumpless extracorporeal system has been well documented in the experimental literature.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports based on our EVE system we demonstrated healthy fetal survival for a period of hours (h), and further extended that to 336 h in a subsequent set of unpublished experiments. [7][8][9][10] Other investigators have reported the successful application of artificial-placenta based therapies for up to h with similar concepts and extracorporeal gas exchange systems. [11][12][13][14] Accordingly, the feasibility of long survival with a pumpless extracorporeal system has been well documented in the experimental literature.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…The ewe's abdomen was clipped to expose the skin and thoroughly prepared for surgery as described previously. 7,9,10,37 Ewes in both the EVE and the control groups were euthanized with an intravenous bolus of pentobarbitone (160 mg/kg).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…With this in mind, researchers are seeking an alternative physiological approach to sustaining underdeveloped human beings by better mimicking the uterine environment to effectively prolong gestation. i 16 This encompasses a support system closer to an AW, facilitating continuing development as if the neonate had never been born , as opposed to infant incubators assisting preterms with bodily functions they cannot perform adequately for themselves.…”
Section: Artificial Wombs—where Are We?mentioning
confidence: 99%
“…A preterm lamb model of an 'artificial placenta,' or ex vivo uterine environment (EVE) therapy, has recently been developed. 7,8,11,17 This model is an artificial version of extracorporeal support of the fetus, which is ordinarily provided by the placenta in utero. 11 Priming of the extracorporeal circuit in these models requires whole blood, and fresh maternal blood is used initially.…”
mentioning
confidence: 99%